FIGURE-BASED POLITICS IN LABORER VOTING BEHAVIORS: A Study of Semarang Industrial Laborers In the 2004-2014 Elections - Hendrawan Toni Taruno (Universitas Sultan Ageng Tirtayasa, 2018)
This study is aimed to explore further how the laborers in Semarang determined their political preferences in the 2004-2014 presidential and legislative elections. As we know, many studies have been conducted to discuss laborers and politics. But few of them discussed laborer voting behaviors in the election. This study uses a quantitative approach and survey method. The survey was conducted to 394 industrial laborers in Semarang city. By using psychological and rational choice models, this study resulted in two major findings. First, the emergence of political consciousness among industrial laborers in the electoral politics. Second, the dominant influence of psychological factors on laborer voting behaviors. From these findings, I argue that the quality of democracy among laborers is relatively good and that figure-based politics, even among laborers, tends to be found wider and seems to be the “new style” of democracy in Indonesia.